2019
DOI: 10.1002/1878-0261.12523
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Cdr1as sensitizes bladder cancer to cisplatin by upregulating APAF1 expression through miR‐1270 inhibition

Abstract: Circular RNAs (circRNAs) have recently emerged as essential regulators in carcinogenesis and cancer progression. Previous studies have shown that Cdr1as functions as a microRNA (miRNA) sponge in various cancer types. However, the role of Cdr1as in cisplatin chemosensitivity in bladder cancer remains unclear. Here, we used real‐time PCR to examine miRNA and gene expression in bladder cancer tissues and cell lines. The abilities of Cdr1as and its downstream regulatory molecules to induce apoptosis and promote ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
94
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 37 publications
(47 reference statements)
4
94
0
1
Order By: Relevance
“…CircRNAs may serve as ceRNAs or sponges for miRNAs to participate in the development of cancers . Several reports have documented that circCDR1as could act as a ceRNA to regulate the processes of tumor cells . In the present study, we confirmed circCDR1as as a sponge of miR‐219a‐5p by dual‐luciferase reporter assay.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…CircRNAs may serve as ceRNAs or sponges for miRNAs to participate in the development of cancers . Several reports have documented that circCDR1as could act as a ceRNA to regulate the processes of tumor cells . In the present study, we confirmed circCDR1as as a sponge of miR‐219a‐5p by dual‐luciferase reporter assay.…”
Section: Discussionsupporting
confidence: 79%
“…32 Several reports have documented that circCDR1as could act as a ceRNA to regulate the processes of tumor cells. 33,34 In the present study, we confirmed circCDR1as as a sponge of miR-219a-5p by dual-luciferase reporter assay. Moreover, we found that miR-219a-5p expression declined in NSCLC and its overexpression repressed NSCLC development in vitro, which was also in agreement with previous studies.…”
Section: Discussionsupporting
confidence: 77%
“…CircRNA-CDR1as is known to act as sponge of multiple miRNAs. Besides miR-7, which has more than 70 binding sites in circRNA-CDR1as, circRNA-CDR1as has been reported to be sponge for miR-135a [31], MiR-1270 [26], and miR135b-5p [27]. In this study, we further expanded the family of its target miRNAs.…”
Section: Discussionmentioning
confidence: 94%
“…Much of the research on OA has focused on its diagnosis, pathogenesis, epigenetic regulation, and potential therapeutic purposes containing microRNAs. With the identification and further functional analysis of circRNA-CDR1as, its function as a sponge for multiple miRNAs has been revealed [14,[22][23][24][25][26][27][28]. But its role in OA development has not been explored previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation